Sandwich structures with cork agglomerate cores for thermal insulation purposes in aircraft - Peixoto, Demis Rodrigues (2014)
As the use of sandwich structures continues to increase rapidly for applications ranging from satellites, aircraft, ships, automobiles, rail cars, wind energy systems, and bridge construction (to mention only a few), lightweight and high strength structures have become indispensable to many high-tech industries such as aerospace, civil infrastructure and vehicle. Therefore, the demand for new materials has been rising which in turn led to the increasing use of composite sandwich structures applications. Utilizing natural materials over traditional synthetic structures allows avoiding the use of oil and other carbon products for the fabrication, which were otherwise needed, thus resulting in a reduction of carbon emissions. Besides being renewable, these materials provide such benefits as being both biodegradable and recyclable. In its simplest form a structural sandwich is composed of two thin stiff face sheets and a thick lightweight core bonded between them. The properties of primary interest for the core materials can be summarized as: low density, high shear modulus, high shear strength, elevated stiffness perpendicular to the faces and both good thermal and acoustic insulation characteristics. The commonly used core materials are foams, balsa wood and honeycombs, the latter consisting in superlight structures with high strength-to-weight and stiffness-to-weight ratios. Honeycombs can be defined as an array of open cells, formed from sheets of suitable material, bonded together at controlled intervals and then expanded to form hexagonal cells. However, recent developments resulted into new alternatives like cellular core structures such as the case of cork. Cork has an alveolar cellular structure similar to that of a honeycomb, and its cells are mostly formed by suberin, lignin and cellulose. Although it seems that natural cork has a poor mechanical behavior when compared with other types of core materials, such as synthetic foams, for some specific applications, cork can actually compete with these materials. Its low thermal conductivity combined with a reasonable compressive strength makes it an excellent material for thermal insulation purposes as well as for applications in which compressive loads are present. The work herein presented aims to study the feasibility of implementing cork, more specifically the NL20 cork agglomerate fabricated by Amorim Cork Composites, as the core material of sandwich structures with aluminum face sheets (Aalco 5754) by thermally characterizing nine circular sandwich panel samples through experimental tests. Taking into account the enormous challenges imposed by the global stake-holders of drastically reducing (75% per passenger/km) the environmental impact, such as the CO2 emissions associated to the current manufacturing, as well as the operational and maintenance technologies of the various ways of transport, it becomes paramount that aeronautical industry starts incorporating a high amount of recyclable components, in addition to being lighter. Therefore, one of the key objectives of this study is to lower the weight of the samples whilst maintaining their thermal characteristics by drilling different hole patterns into their cork cores. The core configurations differ in hole shape, diameter and depth so that their impact could be assessed. However, a uniform sample is included which served as the reference model for all others. The impact of the core´s mass regarding the component´s insulating ability was also investigated. All samples, which are thermally insulated on the sides in order to ensure one dimensional heat flow, were heated up to 80°C on the bottom face sheet and their individual insulating ability was determined by the measurement of the temperature at the center of the top face sheet with a contact thermocouple. The temperature distribution on the top face sheets was also recorded by a thermographic infrared camera positioned above the samples. The numerical analysis were carried out by resorting to the finite element code ABAQUS® v6.10-1. The experimental tests had to be performed first so that the experimental convective heat transfer coefficient could be determined and subsequently used in the numerical analysis. Heat transfer through radiation was proven to have very little influence on the results due to the small temperature differences between the samples and the surroundings, thus being practicably negligible. The conclusions drawn from the comparison between the experimental and the numerical results allow taking an important step towards the adoption of cork as the material of choice for the core of sandwich structures and should serve as basis or reference for future more detailed studies in this area.